Association between baseline body mass index and survival in men with metastatic hormone‐sensitive prostate cancer: ECOG‐ACRIN CHAARTED E3805. Issue 12 (10th May 2022) - Morgans, Alicia K.; Chen, Yu‐Hui; Jarrard, David F.; Carducci, Michael; Liu, Glenn; Eisenberger, Mario; Plimack, Elizabeth R.; Bryce, Alan; Garcia, Jorge A.; Dreicer, Robert; Vogelzang, Nicholas J.; Picus, Joel; et al.
Abstract: Background: E3805 (CHAARTED) is a phase 3 trial demonstrating improved survival for men with metastatic hormone‐sensitive prostate cancer (mHSPC) randomized to treatment with docetaxel (D) and androgen‐deprivation therapy (ADT) versus ADT alone. We assessed the association of baseline body mass index (BMI) and metformin exposure with quality of life (QOL) and prostate cancer outcomes including survival in patients enrolled in the CHAARTED study. Methods: We performed a posthoc exploratory analysis of the CHAARTED trial of men with mHSPC randomized to treatment with ADT with or without D between 2006 and 2012. Cox proportional hazards models and Kruskal–Wallis test were used to evaluate the association between BMI with QOL and prostate cancer outcomes and between metformin exposure and survival. Results: In 788 of 790 enrolled patients with prospectively recorded baseline BMI and metformin exposure status, lower BMI was not associated with survival, but was associated with high volume disease ( p < 0.0001) and poorer baseline QOL on functional assessment of cancer therapy–prostate ( p = 0.008). Only 68 patients had prevalent metformin exposure at baseline in the CHAARTED trial. Four groups were identified: ADT + D + metformin ( n = 39); ADT + D ( n = 357); ADT + metformin ( n = 29); and ADT alone ( n = 363). Baseline clinicopathologic characteristics were similar between groups. In this small exploratory multivariable analysis, metformin exposure was not associated with survival (hazard ratio: 1.15; 95% confidence interval: 0.81–1.63, p = 0.44). Conclusions: There was no link between baseline BMI and survival, but lower baseline BMI was associated with features of greater cancer burden and poorer QOL.